Barriers and motivations of the Ethiopian university instructors for designing and delivering online content - Nahom Eyasu Alemu; Wanjira Kinuthia (Humanities & Social Sciences Communications)
Abstract Digital technologies have consistently focused on online education in developed nations. However, more attention could be paid to the involvement of university instructors in online education in developing countries. In the case of the University of Gondar, Ethiopia, there needs to be more knowledge generated regarding the barriers and motivations these instructors face when designing and creating online content. This research addresses this knowledge gap by examining i) the barriers university instructors face when developing and delivering online content and ii) the motivations behind university instructors designing and delivering online content. This study involved 59 participants. Using purposive sampling, data were collected from lecturers using semi-structured interviews, focus group discussions, and key informants. The data were analysed using inductive thematic analysis to explore participants’ explanations about the impediments and motivation of university instructors in designing and developing content online at the University of Gondar. Explanations were presented regarding barriers (the state of being faced with the barriers of university instructors) and motivation (the determination of instructors in higher education). The findings showed that the challenges of instructors can be classified as personal (technophobia, digital illiteracy, negative impression of content online, fear of making low-quality content, and lack of knowledge on how to produce content online) and institutional (insufficient infrastructure, absence of curriculums and policies on eLearning education. On the other hand, the prospects of instructors, such as eLearning capacity building initiatives, providing online education support services, and boosting awareness of online education, are the facilitators for instructors in developing content online in higher education.